2011
DOI: 10.3109/0284186x.2011.582515
|View full text |Cite
|
Sign up to set email alerts
|

MRI quality assurance using the ACR phantom in a multi-unit imaging center

Abstract: (2011) MRI quality assurance using the ACR phantom in a multi-unit imaging center, Acta Oncologica, 50:6, 966-972,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 12 publications
0
62
0
Order By: Relevance
“…There have been a number of publications of the ACR phantom test conducted on diagnostic MRI scanners (10)(11)(12)(13)(14) for diagnostic MRI QA/QC purpose, while the reports of ACR phantom test on dedicated MR-sim are still sparse (15). Our results showed that ACR phantom image acquired on a 1.5T dedicated MR-sim generally had sufficiently good image quality to pass all ACR recommended criteria, under a compromised flexible coil setting, thus fulfilled the basic requirements for clinical service.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of publications of the ACR phantom test conducted on diagnostic MRI scanners (10)(11)(12)(13)(14) for diagnostic MRI QA/QC purpose, while the reports of ACR phantom test on dedicated MR-sim are still sparse (15). Our results showed that ACR phantom image acquired on a 1.5T dedicated MR-sim generally had sufficiently good image quality to pass all ACR recommended criteria, under a compromised flexible coil setting, thus fulfilled the basic requirements for clinical service.…”
Section: Discussionmentioning
confidence: 99%
“…DXA, QCT, pQCT, HR-pQCT, MRI and QUS to ensure that accuracy and precision of the devices are consistent with manufacture guidelines (174,175). Accuracy is by definition the ability of a measurement to match the actual value of the quantity being measured and it is expressed in terms of accuracy error; precision, expressed in terms of PE, refers to the degree of reproducibility of repeated measurements under unchanged conditions (176).…”
Section: Quality Assurance (Qa) Proceduresmentioning
confidence: 99%
“…MRI is affected by multiple technical and image quality problems and, even if several organizations suggested their QA recommendations and each manufacturer usually uses its own test protocols, the development of universally accepted guidelines would be desirable in MRI (175,(189)(190)(191).…”
Section: Quality Assurance (Qa) Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters should now be evaluated in a multicenter prospective study with a unified imaging protocol. In such a prospective study, the comparability of the imaging results of MRI scanners from different manufacturers can also addressed, since the results may be quite different as shown in the past in other specialties such as oncology [29] . Other technologies to evaluate strictures are DWI (see above) and 'magnetization transfer' (MT)-MRI [30] .…”
Section: Evaluation Of Strictures In CDmentioning
confidence: 99%